Outdoor green, local experience - Abdul Malek, Nurhayati; Mohd Zamri, Norhayati (2012)
The referencing book for local parks and landscape design implementation in Malaysia is lacked and hardly found as most of the current references are developed by the western researchers viewing western cultures and geographic. The main purpose of this study is to identify, compile, review and determine the quality aspects in Malaysian parks and landscape design and produced it in a form of textbook for all Landscape Architecture students and Landscape architect nationwide used. Several research questions have been identified to guide this study which is why do people need parks and open spaces? Why landscape architectural design important? Does good landscape design contribute to better usage? And does good landscape design really affect the quality of life? This study will be focusing on the needs for parks and open space, relevance of landscape architectural design in any developments, relationship between good landscape design and usage and lastly to inspect whether good landscape design will affect the level of quality of life among Malaysian.